Periodontal treatment and glycaemic control in patients with diabetes and periodontitis: an umbrella review (2016)
ABSTRACT: Background: Studies suggest that non-surgical periodontal treatment improves glycaemic control in patients with diabetes and periodontitis. The aim of this umbrella review is to summarize the effects of periodontal treatment on glycaemic control in patients with periodontitis and diabetes. Methods: A systematic review of systematic reviews with or without meta-analysis published between 1995 and 2015 was performed. Three independent reviewers assessed for article selection, quality and data extraction. Results: Thirteen (13) systematic reviews/meta-analysis were included for qualitative synthesis. A reduction (0.23 to 1.03 percentage points) in the levels of HbA1c at 3 months after periodontal intervention was found. This reduction was sta- tistically significant in 10/12 meta-analysis. One review with sufficiently large samples found a non-significant reduction (0.014 percentage points; 95% CI 0.18 to 0.16; p = 0.87). Only three studies separated the use of adjunctive antibi- otics and found a reduction of 0.36 percentage points but the difference was not statistically significant. Conclusions: Highly heterogeneous short-term studies with small sample size suggest that periodontal treatment could help improve glycaemic control at 3 months in patients with type 2 diabetes and periodontitis. However, longer term studies having sufficient sample size do not provide evidence that periodontal therapy improves glycaemic control in these patients.